Cloud testing tools - Xiaoying Bai; Muyang Li; Bin Chen; Wei-Tek Tsai; Gao, J. (2011 IEEE 6th International Symposium on Service Oriented System, 2011)
Cloud platform provides an infrastructure for resource sharing, software hosting and service delivering in a pay-per-use approach. To test the cloud-based software systems, techniques and tools are necessary to address unique quality concerns of the cloud infrastructure such as massive scalability and dynamic configuration. The tools can also be built on the cloud platform to benefit from virtualized platform and services, massive resources, and parallelized execution. The paper makes a survey of representative approaches and typical tools for cloud testing. It identifies the needs for cloud testing tools including multi-layer testing, SLA-based testing, large scale simulation, and on-demand test environment. To address the needs, it investigates the new architecture and techniques for designing testing tools for the cloud and in the cloud. Tool implementations are surveyed considering different approaches including migrated conventional tools, research tools, commercial tools and facilities like benchmark and testbed. Based on the analysis of state-of-the-art practices, the paper further investigates future trend of testing tool research and development from both capability and usability perspectives.